A Rare Pathological Entity of Multiple Calcified Hyperplastic Dental Follicles - Sumith Gunawardane; Kanchana Kapugama (Case Reports in Dentistry)
Multiple calcified hyperplastic dental follicles (MCHDF) are an extremely rare condition which has been categorized as a separate pathological entity very recently. It was initially described by Sandler et al. Gardner and Radden proposed this as a separate pathological entity. This disease is characterized by multiple unerupted teeth with abundant calcifications and rests of odontogenic epithelium in enlarged dental follicles.